2018
DOI: 10.1016/j.jclinepi.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on costs and resource use of randomized clinical trials shows a lack of transparent and comprehensive data

Abstract: The usefulness of the available empirical evidence on resource use and costs of RCTs is limited. Transparent and comprehensive resource use and cost data are urgently needed to support budget planning for RCTs and help improve sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 80 publications
1
61
0
Order By: Relevance
“…In the 3 trials in which the EHR infrastructure was well established and was merely redirected for use in the trials, 18,27,34 the cost per patient (median $44) was much lower than often-reported costs in traditional trials. 41 The costs of the 2 trials in which the infrastructure was less integrated (such as actively screening the EHR for assessing the clinical outcome), a median of $1280 per patient, were more similar to those of traditional RCTs. 24,30 A recently published overview of registry trials showed similar trial cost patterns (i.e., a reduction of costs when the outcome data did not require manual collection but, rather, the registry infrastructure was leveraged).…”
Section: Discussionmentioning
confidence: 99%
“…In the 3 trials in which the EHR infrastructure was well established and was merely redirected for use in the trials, 18,27,34 the cost per patient (median $44) was much lower than often-reported costs in traditional trials. 41 The costs of the 2 trials in which the infrastructure was less integrated (such as actively screening the EHR for assessing the clinical outcome), a median of $1280 per patient, were more similar to those of traditional RCTs. 24,30 A recently published overview of registry trials showed similar trial cost patterns (i.e., a reduction of costs when the outcome data did not require manual collection but, rather, the registry infrastructure was leveraged).…”
Section: Discussionmentioning
confidence: 99%
“…Within a given category of recruitment strategies, for instance, the median cost of a mailed invitation was 228 USD, ranging from 15 to 1,116 USD per patient. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatment uncertainties in neonatal practice [1] that would benefit from being subjected to high-quality randomised clinical trials [2]. However, the high cost of undertaking large and methodologically robust trials [3] means that only a small number are undertaken each year: the median cost of randomised controlled trials was estimated between US$43 and US$103,254 per participant [4] and publicly funded pragmatic neonatal trials cost £1.5-2 million [5]. A key driver of cost in clinical trials is data collection; the mean costs of trial data collection using conventional Case Record Forms have been estimated to be €1135 per participant [6].…”
Section: Introductionmentioning
confidence: 99%